The Social Impact of Drugs on Adolescents' Knowledge and Attitudes - Shojaeizadeh, Davood; Hossein Taghdisi, Mohammad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Adolescents always try to understand themselves and manage their behavior and emotions as much as possible, they will develop a positive self-image, reasoning power and the ability to manage thoughts, emotions and behavior, always trying to overcome the problems or stress they experience. However, teenagers are also inseparable from the attitude and behavior of fad or trial and error and can be curious to know more. Adolescents and youth are the next generation of nation building. The future development of the nation is very dependent on the quality of youth in the future as Human Resources. The purpose of this study was to determine the dangers of drugs in Makassar Vocational High School. This study uses a type of quantitative research with a pre-experimental research design (pre-post test design with one group). The research design used one group, previously a pretest was carried out to measure adolescents' knowledge of the dangers of drugs and then a post test was carried out. This research was conducted at Makassar Vocational High School. The results of the study showed that the age of the respondents was at 15-18 years. Most of the respondents' average age was 16 and 17 years (35%). Most of the respondents (63%) were male and almost half (37%) were female and almost half (46%) their parents worked as civil servants.